Commodity Price Shocks and Global Cycles: Monetary Policy Matters - Efrem Castelnuovo; Lorenzo Mori; Gert Peersman (CESifo GmbH, 2024)
We employ a structural VAR model with global and US variables to study the relevance and transmission of oil, food commodities, and industrial input price shocks. We show that commodities are not all alike. Industrial input price changes are almost entirely endogenous responses to other shocks. Exogenous oil and food price shocks are relevant drivers of global real and financial cycles, with food price shocks exerting the greatest influence. We then conduct counterfactual estimations to assess the role of systematic monetary policy in shaping these effects. The results reveal that pro-cyclical policy reactions exacerbate the real and financial effects of food price shocks, whereas counter-cyclical responses mitigate those of oil shocks. Finally, we identify distinct mechanisms through which oil and food shocks affect macroeconomic variables, which could also justify opposing policy responses. Specifically, along with a sharper decrease in nondurable consumption, food price shocks raise nominal wages and core CPI, intensifying inflationary pressures. Conversely, oil price shocks act more like adverse aggregate demand shocks absent monetary policy reactions, primarily through a decrease in durable consumption and spending on goods and services complementary to energy consumption, which are amplified by financial frictions.
Keywords: E32; E52; F44; G15; Q02; 330; commodity price shocks; transmission mechanisms; monetary policy